Fostering Community Engagement: English Language Lecturers’ Professional Development Through Collaborative Research - Khairatunnisa; Nani Hizriani; Saadillah; Kesya Fitriah Azizah (Majalah Ilmiah UPI YPTK, 2025)
This study examined the creation and effects of a community-based professional development initiative for English language educators at private higher education institutions in South Kalimantan that is administered by the Ministry of Religious Affairs (MORA). There are 3 universities joined in this program with 6 educators who taught English subject in university. Given that English language teaching (ELT) required collaborative research abilities, the project offers workshops on multidisciplinary communication, project management, and publication in addition to comprehensive instruction in research methods, data analysis, and ethical practices. The program enables educators to actively participate in community-focused research and pedagogical developments by fostering a culture of knowledge-sharing and cooperation through networking and mentoring opportunities. Using a service-learning methodology, the project combined academic goals with community involvement, strengthening social engagement and professional skills. Then, the participants did the activities for eight meetings for several stages such as primary planning, supply and instruction, getting familiar with journals, reference searching, and the last journal publications. Results demonstrated that organized phases such as planning, teaching, and publishing preparation enable teachers to develop their skills and gain authority. Next, the participants are able to conduct the research using the previously taught method.